Boil the Plan, But Do Not Fry The Issue; Indonesian Cooking Terms Metaphor - Muhammad Adam; Rosmiati Rosmiati (LPPM Universitas Bina Sarana Informatika, 2020)
Cultural aspect and experiential basis is two of the components in the metaphor production. Several studies have been conducted in conceptual metaphor framework, but there haven’t many of the studies relate how the daily Indonesian cultural life affects the metaphor production. This paper aims to focus on the use of Indonesian cooking terms in media news headlines. The conceptual metaphor theory (Lakoff and Johnson, 1980) is used as the theoretical framework. Qualitative method is used during this study with purposive sampling data collection method. The source of the data is ten news headlines from Indonesian online media news that use cooking terms metaphor. The result shows that the metaphorical use of Indonesian cooking terms come from two types, the first is the level of cooking with words mentah (raw/undercooked), and matang (fully cooked) to describe a progress of a plan or policy draft, and the second type is process of cooking by using godok (to boil) and goreng (to fry) but with a different target domain. The result also shows that the use of godog (to boil) as metaphor refer to a plan or a program that are being prepared and being discussed and implies a positive association, whereas the metaphorical use of menggoreng (to fry) tends to be more negative as it refers to an exaggerated (political) issue.